Nitrogen fertilization challenges the climate benefit of cellulosic biofuels - Ruan, Leilei; Bhardwaj, Ajay K; Hamilton, Stephen K; Robertson, G Philip (Environmental research letters, 2016)
Cellulosic biofuels are intended to improve future energy and climate security. Nitrogen (N) fertilizer is commonly recommended to stimulate yields but can increase losses of the greenhouse gas nitrous oxide (N2O) and other forms of reactive N, including nitrate. We measured soil N2O emissions and nitrate leaching along a switchgrass (Panicum virgatum) high resolution N-fertilizer gradient for three years post-establishment. Results revealed an exponential increase in annual N2O emissions that each year became stronger (R2 > 0.9, P < 0.001) and deviated further from the fixed percentage assumed for IPCC Tier 1 emission factors. Concomitantly, switchgrass yields became less responsive each year to N fertilizer. Nitrate leaching (and calculated indirect N2O emissions) also increased exponentially in response to N inputs, but neither methane (CH4) uptake nor soil organic carbon changed detectably. Overall, N fertilizer inputs at rates greater than crop need curtailed the climate benefit of ethanol production almost two-fold, from a maximum mitigation capacity of −5.71 0.22 Mg CO2e ha−1 yr−1 in switchgrass fertilized at 56 kg N ha−1 to only −2.97 0.18 Mg CO2e ha−1 yr−1 in switchgrass fertilized at 196 kg N ha−1. Minimizing N fertilizer use will be an important strategy for fully realizing the climate benefits of cellulosic biofuel production.